Application of Blockchain Technology in Water Rights Trading in the Irrigation Area under the Internet-of-Things Environment. (12th August 2022) - Li, Yang; Xie, Jiancang; Yang, Jianghua; Ren, Jian; Zhai, Nan
Abstract : Water rights trading is an important way to solve the shortage of water resources. Combined with the characteristics of water resources and the requirements of the market economy, the organic combination of the government and the market should be strengthened. Through the establishment of a water rights system and a water rights trading market, the implementation of water rights trading will be promoted. Due to the decentralized and distributed structure, blockchain technology greatly reduces its intermediary cost in the application process. The tamper-resistant timestamp feature can realize data tracking and information anticounterfeiting, and flexible programming attributes can promote the specification of market order. Firstly, the reasons for water rights trading are studied, and the water rights trading system is analyzed. It is found that the system has the problems of the cumbersome transaction process and high transaction costs. According to the characteristics of water rights trading, the alliance chain Hyperledger Fabric is selected as the underlying network system of the trading system. Secondly, combined with water rights trading, Hyperledger Fabric multichannel technology is used to design a three-channel accounting method, and the chain code for water rights trading is designed and implemented based on the Go language. CouchDB is adopted to store key-value data, and Ubuntu, Docker, and Docker Compose are used to construct an operating environment of the chain code. Finally, the proposed system is tested. The test findings reveal that the distributed water volume of experimental area 1 is 41.8368 million m 3, the current water volume is 23.831 million m 3, and the quota management water volume is 20.432 million m 3 . The distributed water volume in area 2 is 40.4605 million m 3, the current water volume is 4317.64 m 3, and the quota management water volume is 77.4795 million m 3 . The distributed water volume in area 3 is 65.6928 million m 3, the current water volume is 77.472 million m 3, and the quota management water volume is 64.412 million m 3 . The water rights trading system based on Hyperledger Fabric can record each transaction data, which can be stored in each node, and the data stored in each node are the same. The proposed scheme provides a certain reference for the application of blockchain technology in water rights trading in irrigation areas.